2011
DOI: 10.1044/1092-4388(2011/10-0154)
|View full text |Cite
|
Sign up to set email alerts
|

Visual Cues and Listening Effort: Individual Variability

Abstract: Overall, the results support the hypothesis that integrating auditory and visual cues requires cognitive resources in some participants. The data indicate that low lipreading ability or low WMC is associated with relatively effortful integration of auditory and visual information in noise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
118
4
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(134 citation statements)
references
References 73 publications
7
118
4
5
Order By: Relevance
“…Further, the older adults had lower reading span scores than young adults, indicating that they had lower WMC. Thus, the finding of greater benefit of visual cues by young adults is in line with that of Picou et al (2011) who found that only persons with high WMC derived benefit from the presence of visual cues. This pattern of findings suggest that when executive processing demands are high, as found in the CSCT, visual cues compensate for the reduction in CSC attributable to noise.…”
Section: Reanalysissupporting
confidence: 86%
See 4 more Smart Citations
“…Further, the older adults had lower reading span scores than young adults, indicating that they had lower WMC. Thus, the finding of greater benefit of visual cues by young adults is in line with that of Picou et al (2011) who found that only persons with high WMC derived benefit from the presence of visual cues. This pattern of findings suggest that when executive processing demands are high, as found in the CSCT, visual cues compensate for the reduction in CSC attributable to noise.…”
Section: Reanalysissupporting
confidence: 86%
“…Furthermore, older adults also showed decreased neural activation with visual cues, indicating a processing benefit in terms of less cognitive resources used in the presence of visual cues. Picou et al (2011) found that the person with low WMC did not derive any benefit from the presence of visual cues whereas person with high WMC did derive benefit from the presence of visual cues in cued recall of words. Sommers, Tye-Murray and Spehar (2005) found that the AV integration for speech perception in noise was similar across young and older adults with normal hearing, but the young adults had better speech reading skills compared to older adults and hence had better performance in the AV modality.…”
Section: Visual Cuesmentioning
confidence: 88%
See 3 more Smart Citations